2021
DOI: 10.1002/ecs2.3845
|View full text |Cite
|
Sign up to set email alerts
|

Topography modifies the effect of land‐use change on soil respiration: A meta‐analysis

Abstract: Soil respiration is controlled by land‐use changes associated with cropland vegetation restoration, and this can vary with topography, although the magnitude of this effect and the underlying mechanisms are still unclear. We synthesized 69 recently published papers from China to explore the influence of topography‐related changes in land use on soil respiration where croplands were converted into orchards (abbreviated as C‐O), grasslands (abbreviated as C‐G), or woodlands (abbreviated as C‐W). Our results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Zhang et al, 2020), vegetation (X. Chen & Chen, 2019;Y. Zhang et al, 2021), microplastics (X. , metallic nanoparticles (He et al, 2024), and acid rain (Feng et al, 2017) are not shown.…”
Section: Global-scale Data and Analysesmentioning
confidence: 97%
See 1 more Smart Citation
“…Zhang et al, 2020), vegetation (X. Chen & Chen, 2019;Y. Zhang et al, 2021), microplastics (X. , metallic nanoparticles (He et al, 2024), and acid rain (Feng et al, 2017) are not shown.…”
Section: Global-scale Data and Analysesmentioning
confidence: 97%
“…Additional columns give the number of experimental pairs ( N ) and range of study durations (years) in each meta‐analysis. Meta‐analyses of more rarely examined factors such as fire (Gui et al., 2023; M. Hu et al., 2020), phosphorous (Feng & Zhu, 2019; X. Lu et al., 2022), topography (Y. Zhang et al., 2021), litter inputs (X. Chen & Chen, 2018; Y. Zhang et al., 2020), vegetation (X. Chen & Chen, 2019; Y. Zhang et al., 2021), microplastics (X. Liu et al., 2023), metallic nanoparticles (He et al., 2024), and acid rain (Feng et al., 2017) are not shown.…”
Section: Global‐scale Data and Analysesmentioning
confidence: 99%
“…In fact, spatial heterogeneity of SR was influenced by various soil factors, such as soil nutrient availability (Liang et al, 2021;Xiao et al, 2021), soil C/nitrogen (N)ratio (Cui et al, 2021), soil moisture and temperature (Numa et al, 2021). Moreover, soil topography was regarded as the main factor that was involved the induction of spatial variation of SR (Zhang et al, 2021). Topography, generated a local microclimate, led to variations in soil drainage and SOC distribution, and a change in the soil moisture and temperature, which directly influenced SR (Kang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…At the global scale, Rs has obvious zonal characteristics that are mainly affected by zonal changes in vegetation and climate [8,9]. At the regional scale, landscape [10,11], land use type [12,13], and vegetation type [14,15] affected Rs. At the plot scale, stand and canopy structure [16,17], root distribution [18], and the heterogeneity of major environmental factors and soil characteristics [19] lead to the spatial heterogeneity of Rs [20,21].…”
Section: Introductionmentioning
confidence: 99%